Serum magnesium levels in newly diagnosed type 2 diabetes mellitus and its relation with microvascular complications of diabetes - Bhardwaj, Vinay; Kaushik, Madan Lal (International Journal of Research in Medical Sciences, 2020)
Background: Prevalence of hypomagnesaemia is significantly higher in diabetic patients with microvascular complications compared to diabetics with no microvascular complications. The aim of this study is to measure levels of serum magnesium in patients with newly diagnosed type 2 diabetes mellitus and study its association with the presenting microvascular complications. Methods: This was hospital based, one year cross-sectional study carried out in Department of Medicine, IGMC Shimla in patients with newly diagnosed type 2 diabetes mellitus. Total 53 patients were enrolled in this study who presented in medicine OPD or admitted in medicine ward. Results: Serum Magnesium value of the patients ranged from 1.20-3.0 mg/dl with mean value of 1.9±0.3 mg/dl. Fourteen patients (26.4%) had hypomagnesaemia. A total of 34 (64.2%) patients presented with complications of diabetes in which proteinuria was present in 34 (64.2%), retinopathy in 4 (7.5%) and neuropathy in 1 (1.9%). Fourteen (41.2%) patients with hypomagnesaemia presented with complications of diabetes (p value=0.003). 34 (64.2%) patients presented with proteinuria out of which 14 (41.2%) patients had hypomagnesaemia while 20 (58.8%) had normomagnesaemia (p=0.03). One (1.9%) patient had neuropathy and hypomagnesaemia was also present in this patient (p=0.6). Four patients (7.5%) presented with retinopathy out of which 3 (5.7%) had hypomagnesaemia while 1 (1.9%) had normomagnesaemia. Conclusions: Hypomagnesaemia is associated with microvascular complications of diabetes. Also there is statistically significant relationship between proteinuria and hypomagnesaemia in patients with newly diagnosed type 2 diabetes mellitus.